B-Cell-Depleting Immune Therapies as Potential New Treatment Options for Systemic Sclerosis - Gerhard Zugmaier; Matthias Klinger; Marion Subklewe; Faraz Zaman; Franco Locatelli (Sclerosis)
Background: Systemic sclerosis (SSc), also known as scleroderma, is a complex, chronic autoimmune disease characterized by fibrosis of the skin and internal organs, vasculopathy, and immune system dysregulation. The treatment of SSc has historically focused on symptom management and slowing down disease progression through conventional immune-suppressive agents. New therapeutic approaches have been emerging due to advances in understanding of the disease mechanisms, particularly in the areas of fibrosis, vascular involvement, and immune dysregulation. Methods: In this review of the literature, we discuss the current stage of development of B-cell-depleting immune therapies in SSc. Results: B-cell depletion therapy has become an area of growing interest in the treatment of SSc due to the role played by B cells in the pathogenesis of the disease. There is increasing evidence that B cells contribute to disease progression through multiple mechanisms. B cells in SSc are implicated in autoantibody production, cytokine production, and fibroblast activation. B cells are responsible for producing autoantibodies, such as anti-topoisomerase I (Scl-70) and anti-centromere antibodies, which are hallmarks of SSc. B cells release pro-inflammatory cytokines (such as interleukin-6 [IL-6] and transforming growth factor β [TGF-β]), which promote fibrosis and inflammation, they also contribute to the activation of fibroblasts, the cells responsible for excessive collagen production and fibrosis, a key feature of SSc. Conclusions: In light of these findings, therapies that target B cells are being investigated for their potential to modify the disease course in SSc, particularly by reducing autoantibody production, inflammation, and fibrosis.